2021
DOI: 10.1038/s41598-021-85643-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Crabtree negative yeast from rumen fluids can improve rumen fermentation and milk quality

Abstract: Upgrading the nutritive value of rice straw (RS) is necessary to increase its contribution to enhancing meat and milk production. Present work verified whether novel Crabtree negative yeast inoculant could promote RS utilization, rumen fermentation, and milk quality in tropical crossbred lactating Holstein cows. The new stain of Crabtree negative yeasts (Pichia kudriavzevii KKU20 and Candida tropicalis KKU20) was isolated from the rumen of dairy cattle. This study used 6 multiparous crossbreds between Holstein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Dietary composition has the greatest influence on volatile fatty acid content; manipulating the diet by increasing the level of concentrate diet is a strategy to improve ruminal fermentation by increasing propionogenesis [ 45 ]. Such a typical propionic acid fermentation reaction was found in the current investigation, and as a result, the C 2 :C 3 ratio decreased, which is consistent with prior findings [ 4 , 46 , 47 , 48 ]. This increase in C 3 concentration can be attributed to increased nonfiber carbohydrate consumption.…”
Section: Resultssupporting
confidence: 93%
“…Dietary composition has the greatest influence on volatile fatty acid content; manipulating the diet by increasing the level of concentrate diet is a strategy to improve ruminal fermentation by increasing propionogenesis [ 45 ]. Such a typical propionic acid fermentation reaction was found in the current investigation, and as a result, the C 2 :C 3 ratio decreased, which is consistent with prior findings [ 4 , 46 , 47 , 48 ]. This increase in C 3 concentration can be attributed to increased nonfiber carbohydrate consumption.…”
Section: Resultssupporting
confidence: 93%
“…In addition, yeast can competitively bind to the binding sites in the gastrointestinal tract with the toxins produced by pathogenic bacteria and help to eliminate the toxins, which is advantageous to enhance the growth performance of cattle (Ma et al, 2021). It has also been found that the addition of brewer's yeast to cattle diets can improve the microecological environment of the rumen, regulate the pH in the rumen, increase feed conversion, and thus improve the performance of cattle (Suntara et al, 2021). Meanwhile, cellulase was also more commonly used in beef cattle production, and had a good promotion effect on the performance of beef cattle (Dehghan-Banadaky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have also recorded the qualitative improvement in milk production using probiotic interventions. A study conducted on lactating Holstein cows by Suntara et al (2021b) presented an interesting fact that administration of animal feed prepared with Crabtree-negative yeast ( P. kudriavzevii KKU20 and C. tropicalis KKU20) increased the milk protein content. The reason was connected to the increased beneficial microbial population in the rumen, which enhanced the amount of microbial crude protein.…”
Section: Probiotics To Improve the Productivity Of Dairy Animalsmentioning
confidence: 99%